2009
DOI: 10.1111/j.1365-2141.2009.07761.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytolytic T‐cell response to the PASD1 cancer testis antigen in patients with diffuse large B‐cell lymphoma

Abstract: SummaryThe identification of immunogenic cancer testis antigens (CTAs) as immunotherapeutic targets represents one approach to improve treatment options for diffuse large B-cell lymphoma (DLBCL). We previously identified PASD1 [PAS (Per ARNT Sim) domain containing 1 (PASD1)], a DLBCLassociated CTA that was expressed in a range of hematopoietic malignancies. The aim of the present study was to investigate the presence of a cytotoxic T-cell (CTL) response to PASD1 in DLBCL patients. A significant cinterferon (IF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 45 publications
1
31
0
Order By: Relevance
“…23 Peptide PASD1(7) also elicited a CD4 Th response in patient 24, despite a previous observation that no CTL response was detected in this HLA-A*0201-positive patient. 22 Furthermore, an interferon-γ response was also detected in six other DLBCL patients who were HLA-A*0201-negative. While the number of patients studied here was relatively small, ten of the 15 patients with a CD4 Th response remain in complete remission, one is in partial remission and four have died (one of carcinoma).…”
Section: Detection Of Interferon-γ Releasementioning
confidence: 91%
See 2 more Smart Citations
“…23 Peptide PASD1(7) also elicited a CD4 Th response in patient 24, despite a previous observation that no CTL response was detected in this HLA-A*0201-positive patient. 22 Furthermore, an interferon-γ response was also detected in six other DLBCL patients who were HLA-A*0201-negative. While the number of patients studied here was relatively small, ten of the 15 patients with a CD4 Th response remain in complete remission, one is in partial remission and four have died (one of carcinoma).…”
Section: Detection Of Interferon-γ Releasementioning
confidence: 91%
“…18 We initially identified PASD1 as a tumor-associated antigen in DLBCL 19 and acute myeloid leukemia 20 while later studies showed PASD1 to be a novel cancer-testis antigen expressed in a wide range of hematologic malignancies. 21,22 Our subsequent identification of a CTL response to PASD1 in DLBCL 23 supports this molecule as a candidate for vaccine development, not only for DLBCL, but also for use in a generic vaccine for the treatment of other PASD1-positive malignancies. The current study was performed to investigate the CD4 Th response in DLBCL patients to obtain further support for the inclusion of PASD1 in a lymphoma vaccine.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…There are a number of assays which can be used to validate the expression of antigens in tumour cells. Many of the most frequently used rely on an available antibody which has been validated [50,51]. Techniques frequently used include:-…”
Section: Validation Of the Expression Of Tumour Antigens In Tumour Cellsmentioning
confidence: 99%
“…Amino acids that are considered as having an adverse effect on binding have a coefficient of -1 to -3 [60]. SYFPEITHI database gets updated regularly and has been used to identify various ligands; p28 peptide as an epitope for the CT antigen PLAC1 in breast cancer [61], p101-111 is the first CTA-derived peptide which induces CD4(+), CD8(+), and B-cell responses in vitro [62], p43-57 epitope stimulates T cells in HCA587-derived tumours [63] and PASD1(1) -PASD1(5) [51].…”
Section: The Syfpeithimentioning
confidence: 99%